Smart Poultry Farming: A Mobile-Based IoT System for Real-Time Broiler Monitoring and Management - Nalendra, Adimas Ketut; Waspada, Heri Priya (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
The integration of digital technologies in broiler chicken farming offers practical solutions to persistent challenges such as environmental monitoring, feed management, and livestock health. This study presents the development of a mobile-based broiler farming information system integrated with Internet of Things (IoT) devices to enhance operational efficiency, particularly for small- and medium-scale farmers. The system provides real-time monitoring and control via mobile devices, featuring environmental condition tracking, feed and water level notifications, inventory management, and performance analytics. There was a use of waterfall software development methodology with phases of requirements analysis, system design, implementation, testing, deployment, and maintenance. The system makes use of an ESP32 microcontroller, DHT22 temperature and humidity sensors, MQ-135 ammonia gas sensors, and ultrasonic sensors for feed and water level monitoring. The data from the sensors is transferred to a cloud server and is fetched through a user-friendly mobile application. Tests indicate that the system supports effective real-time monitoring of coop conditions, feed and water control, and prompt response to environmental variations by means of automated alerts. It also supports decision-making through access to past data and performance reports. Despite these advantages, there are still limitations pertaining to internet connectivity, sensor stability, and farmer computer literacy. The novelty of this research is its comprehensive, mobile-accessible IoT solution that combines environmental monitoring with the large-scale farm management operations, completing shortcomings of earlier systems with specialized, isolated monitoring.